2022
DOI: 10.1021/jacs.2c02619
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time High-Sensitivity Reaction Monitoring of Important Nitrogen-Cycle Synthons by 15N Hyperpolarized Nuclear Magnetic Resonance

Abstract: Here, we show how signal amplification by reversible exchange hyperpolarization of a range of 15N-containing synthons can be used to enable studies of their reactivity by 15N nuclear magnetic resonance (NO2 – (28% polarization), ND3 (3%), PhCH2NH2 (5%), NaN3 (3%), and NO3 – (0.1%)). A range of iridium-based spin-polarization transfer catalysts are used, which for NO2 – work optimally as an amino-derived carbene-containing complex with a DMAP-d 2 coligand. We harness long 15N spin-order lifetimes to probe in si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 129 publications
(330 reference statements)
1
16
0
Order By: Relevance
“…A recent study on SPAAC by Ducket's group has revealed that 15 N isotope phenyl azide (Ph- 15 N 3 ) contained long T1 values enabling strong hyperpolarization when reacting with BCN. 49 It is claimed that this data depicts the successful examination of SPAAC reactions, as it con rms the possibility to show 15 N signals for the phenyl azide and the triazole, simultaneously. Another study presents the hyperpolarization of triazole containing antifungal drugs and, thus, deducing detailed hyperpolarization mechanisms for both 1 H and 15 N nuclei.…”
supporting
confidence: 55%
See 2 more Smart Citations
“…A recent study on SPAAC by Ducket's group has revealed that 15 N isotope phenyl azide (Ph- 15 N 3 ) contained long T1 values enabling strong hyperpolarization when reacting with BCN. 49 It is claimed that this data depicts the successful examination of SPAAC reactions, as it con rms the possibility to show 15 N signals for the phenyl azide and the triazole, simultaneously. Another study presents the hyperpolarization of triazole containing antifungal drugs and, thus, deducing detailed hyperpolarization mechanisms for both 1 H and 15 N nuclei.…”
supporting
confidence: 55%
“…They also have the additional bene t of attenuating the effect of relaxation. 49 Signal enhancement is effective for non-deuterated triazole derivatives (Figure S5). Compared with Methanol, DMSO can penetrate biological membranes, such as human skin, affecting the lipid structure and causing bilayer breaks.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…887 In another study, SABRE was employed to monitor chemical synthesis of methyl 2-(nicotinamide) acetate, 888 providing signal enhancements over 130-fold with 50%enriched p-H 2 . Most recently, SABRE was utilized 889 to produce high levels of 15 N hyperpolarization of a range of important nitrogen-containing synthons, such as NO 2 − , PhCH 2 NH 2 , ND 3 , NaN 3 , and NO 3 − , all exhibiting sufficiently long T 1n times to permit detection of hyperpolarized products and intermediates upon their chemical transformations to a range of potentially useful nitrogen-rich products.…”
Section: Chemicalmentioning
confidence: 99%
“…SABRE is also being used for reaction monitoring applications. 126–128 This was illustrated by Halse, Duckett and co-workers, who monitored the activation of the SABRE catalyst and proton-deuterium exchange in a SABRE hyperpolarised substrate. 126 This was achieved with single-shot measurement of hyperpolarisation lifetimes for several protons in the substrates, which reflect both the extent of catalyst activation and the degree of substrate deuteration.…”
Section: Concentrationsmentioning
confidence: 99%